Characterization of response mapping to the Sars-CoV2 (Covid-19) pandemic at first level of care as a public health measure (GnosisWisdom, 2023)
The presence of the pandemic by Covid-19 aroused the interest of the health system which is facing the difficulty of providing access, coverage and timely response to the needs of the population in the first level of care-PNA, the latter, For many years it was focused and designed to solve maternal and child health problems, thus not reaching the great deployment in times of pandemic.Objective To determine the health response capacity in the face of the SarsCov2 (Covid-19) pandemic in the first level of care IPRESS as a public health measure.Materials and Methods A cross-sectional, quantitative approach study was carried out, the level of research reached is descriptive, the method used is inductive and the design that guided the statistical process is non-experimental, cross-sectional. The sample consisted of 79 of the health personnel of the Institutions Providers of Health Services-IPRESS of the first level of care, the technique used was the survey and the instrument the questionnaire.Results The results found on the response capacity of the first-level IPRESSs were observed that 62.5% of the C.S. San Cristóbal perceive that the response to the pandemic by Sars-CoV-2 (Covid-19), 57.1% and 55.6%; They also consider that the response to Covid-19 is regular.Conclusions The response capacity of the IPRESS first level of care is generally regular.
Keywords: COVID-19; Coronavirus; First Level of Health Care; Family and Community Medicine; Community Medicine